Innovate, Automate, Elevate: Web-Based Solutions for Business Process Enhancement in Clinic Appointment System - Muhammad Nasri Mahmod,; MOKHTAR, RASHIDAH; Hasiah Mohamed, (Applied Information Technology And Computer Science, 2024)
In an era defined by technological innovation, this study presenting a comprehensive exploration of design principles and functionalities that govern the development of clinic appointment management through the lens of cutting-edge web-based architecture. The research encompasses the entire developmental spectrum, addressing key components such as system architecture, user interface design, functionality and database integration, elucidating how these components synergize to streamline business processes. Real-world case studies and practical implementations are examined to illustrate the adaptability and effectiveness of the proposed system, showcasing its capacity to revolutionize scheduling processes, reduce wait times, and enhance overall patient satisfaction. Experts analysed the system to validate its design and functionality. User evaluation also been conducted using System Usability Scale (SUS) and the result is 72.5 which indicate the system is good. This study incorporates to the growing body of knowledge in healthcare informatics by providing insights into the strategic fusion of technology and business processes, providing valuable guidance for healthcare administrators, practitioners, and technology developers looking to leverage web-based solutions for improved clinic management.